Cluster-based Improved Sorghum Production and Commercialization in Nyangatom Woreda of South Omo Zone, Southern Ethiopia - Tadesse, Awoke; Adicha, Asmera; Yosef, Tekle; Tadesse, Anteneh (Research on World Agricultural Economy, 2023)
Cluster-based improved sorghum (Melkam variety) production and commercialization was demonstrated in Nyanghtom Woreda of the South Omo Zone for one year (2021) to improve agro-pastoralists' awareness, enhance the adaptation of full-package production technologies, and increase the economic visibility of improved sorghum cultivation. The production was started in a single kebele with a 7-hectare area of coverage. Twenty-five purposively selected direct beneficiaries and twenty-five randomly selected indirect beneficiaries from a neighbor were involved in the production. Direct beneficiaries cultivated sorghum on 0.28 hectares of land. At various stages of crop growth, monitoring, evaluation, and fieldwork were done by both beneficiaries and indirect beneficiaries. Face-to-face interviews with sorghum producers and non-producers were undertaken. Simple descriptive statistics were used to examine quantitative data, like grain yield, whereas the Likert scale was used for qualitative data such as agro-pastoralists perceptions. The result revealed that 30 quintal sorghum grain yield per hectare was obtained from improved sorghum (Melkam variety). The average return obtained from the sale of sorghum grain per hectare was 120,144 ETB. Agropastoralists' perception result revealed that the "Melkam" variety is a higher yielder, and early matured as compared to local. Therefore, cluster-based sorghum production should be promoted for local sorghum growers in order to improve sorghum production sustainability and also seed system should take into account the provision of improved Melkam variety seed. ER